One-step sintering process for the production of magnetocaloric La(Fe,Si)₁₃-based composites - Zhong, Xi-Chun (2023)
A one-step sintering process was developed to produce magnetocaloric La(Fe,Si)13/Ce-Co composites. The effects of Ce2Co7 content and sintering time on the relevant phase transformations were determined. Following sintering at 1373 K/30 MPa for 1–6 h, the NaZn13-type (La,Ce)(Fe,Co,Si)13 phase formed, the mass fraction of α-Fe phase reduced and the CeFe7-type (La,Ce)(Fe,Co,Si)7 phase appeared. The mass fraction of the (La,Ce)(Fe,Co,Si)7 phase increased, and the α-Fe phase content decreased with increasing Ce2Co7 content. However, the mass fraction of the (La,Ce)(Fe,Co,Si)7 phase reduced with increasing sintering time. The EDS results showed a difference in concentration between Co and Ce at the interphase boundary between the 1:13 phase and the 1:7 phase, indicating that the diffusion mode of Ce is reaction diffusion, while that of Co is the usual vacancy mechanism. Interestingly, almost 100 % single phase (La,Ce)(Fe,Co,Si)13 was obtained by appropriate Ce2Co7 addition. After 6 h sintering at 1373 K, the Ce and Co content in the (La,Ce)(Fe,Co,Si)13 phase increased for larger Ce2Co7 content. Therefore, the Curie temperature increased from 212 K (binder-free sample) to 331 K (15 wt.% Ce2Co7 sample). The maximum magnetic entropy change (−∆SM)max decreased from 8.8 (binder-free sample) to 6.0 J/kg∙K (15 wt.% Ce2Co7 sample) under 5 T field. High values of compressive strength (σbc)max of up to 450 MPa and high thermal conductivity (λ) of up to 7.5 W/m∙K were obtained. A feasible route to produce high quality La(Fe,Si)13 based magnetocaloric composites with large MCE, good mechanical properties, attractive thermal conductivity and tunable TC by a one-step sintering process has been demonstrated.